AGE-RELATED ANTLER CHARACTERISTICS IN AN INTENSIVELY MANAGED AND NUTRITIONALLY STRESSED MOOSE POPULATION - Young, Jr., Donald D.; Boertje, Rodney D. (Lakehead University, 2018)
We studied age-related antler characteristics of moose (Alces alces) in Alaska Game Management Unit 20A (during 2007–2010) because of concerns about poor antler development given the population’s high density and unusually low nutritional status. A comparative study was conducted in and near our study area in the early 1970s, when moose density was lower and nutritional status was moderate. Poor antler development was an important concern for 2 reasons: 1) low annual recruitment of bull moose into the harvestable 50-inch (127-cm) antler class in the study area might restrict local harvest when the “Intensive Management” harvest objective was to specifically reduce moose density, and 2) retarded antler growth in yearling and 2-year-old bulls could bias bull:cow and yearling:cow ratios. Regression analysis of antler spread over age indicated that average antler spreads of 50 inches (127 cm) occurred when bulls reached an estimated age of 6.0 years. When using corrected annuli counts of known-age animals, bulls reached antler spreads of 50 inches (127 cm) at 5.6 years of true age in the 1970s versus 6.2 years in this study. We surmised that the difference of <1 year was not a significant management concern, particularly given the wide variation in antler spread in each age class. As a result, we retained a strategy that restricted harvest largely to bulls with antler spreads ≥50 inches (127 cm). During low-level aerial surveys, 22% (11/51) of known-aged, radio-collared yearling bulls, had spiked antlers ≤3 inches (7.6 cm) in length, which likely resulted in their misclassification as females during standard surveys. Presumably, 19% (8/43) of known-age, 2 year-old bulls would probably be misclassified as yearling bulls based solely on brow and main palm separation, the primary characteristic used to distinguish between yearling and 2 year-olds. When antler spread and antler length were used as primary aerial classification criteria, we correctly classified all known-aged, 2 year-old bulls. We recommend survey ...